Efficacy and Safety of Once-Weekly Semaglutide for the Treatment of Type 2 Diabetes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Shi, Fang-Hong; Li, Hao; Cui, Min; Zhang, Zai-Li; Gu, Zhi-Chun; Liu, Xiao-Yan (Frontiers in Pharmacology, 2018)
Background: Semaglutide, a newly once-weekly glucagon like peptide-1 (GLP-1) receptor agonist, has showed a favorable effect on glycaemic control and weight reduction in type 2 diabetes mellitus (T2DM). This meta-analysis was conducted to evaluate the clinical efficacy and safety of semaglutide in T2DM. Methods: A comprehensive searching was performed for Phase III randomized controlled trials (RCTs) which reported the efficacy and safety data of semaglutide and other therapies. The efficacy data expressed as weight mean difference (WMD) and the safety data expressed as risk ratios (RRs) were calculated by employing random-effects model. Heterogeneity was assessed through I2 test, and subgroup analyses were performed by different control groups, dosage of semaglutide and durations of follow up. Results: 9 RCTs including 9773 subjects met the inclusion criteria. For efficacy, compared with other therapies, semaglutide resulted in a significant reduction in glycosylated hemoglobin (weight mean difference, WMD: -0.93%, 95% CI: -1.24 to -0.62, P < 0.001), fasting plasma glucose (WMD: -1.15mmol/L, 95% CI: -1.67 to -0.63, P < 0.001), mean self-monitoring of plasma glucose (WMD: -1.19mmol/L, 95% CI: -1.68 to -0.70, P < 0.001), body weight (WMD: -3.47kg, 95% CI: -3.96 to -2.98, P < 0.001), body mass index (WMD: -1.25 kg/m2, 95% CI: -1.45 to -1.04, P < 0.001), systolic blood pressure (WMD: -2.55 mmHg, 95% CI: -3.22 to -1.88, P < 0.001), with the exception of negative result of diastolic blood pressure (WMD: -0.29 mmHg, 95% CI: -0.65 to 0.07, P = 0.113) and increased impact on pulse rate (WMD: -2.21, 95% CI: 1.54 to 2.88, P < 0.001). The results were consistent across the key subgroups. For safety, semaglutide did not increase the risk of any adverse events, hypoglycemia and pancreatitis, but induced a higher risk of gastrointestinal disorders when compared with other therapies (RR: 1.98, 95%CI: 1.49 to 2.62, P < 0.001). Conclusion: Semaglutide was effective and acceptable in patients with T2DM except for a high risk of gastrointestinal disorders. The capacity of glycaemic and body weight control of semaglutide appeared more effective than other add-on therapies including other GLP-1 receptor agonists of exenatide release and dulaglutide.